The care for humanity, a look out since the anthropology of tenderness - Guillermo Meza Salcedo (Universidad de Alicante, 2019)
Introduction: From the of birth, everyone humans are thrown into the world in a helpless, vulnerable, dependent manner. Without the care of another, whether strange or near, we could not survive. We are dependent on others, we depend on their recognition, their cares, their displays of affection, their tenderness. Objective: To analyse the anthropological link between care and tenderness to potentiate care as an essential "way to be" of the human being, who ontological way was born of care and needs care. Methodology: A qualitative documentary research with a hermeneutic approach is carried out. Once the bibliographic material that addresses the categories of care, tenderness and love is selected, an analysis is made of what is interwoven in them, always in relation to the human being. Results and discussions: Results and discussions: The study carried out puts in close anthropological relation to the care with the tenderness. Both are a fundamental part of the human being as supply and demand, as a basic need, without which the person would can´t to live his humanity in fullness. In addition, in this relationship between tenderness and care, love is also interwoven as an essential note for care. It is also analysed that what gives us existence is the feel not the think, an existence that requires care not as sentimentality but as vigour. Conclusions: Through tenderness, care can be offered with greater generosity and sensitivity, with all the vigour that it carries within and springs from itself when worries, anticipating and feeling affected by the carelessness and the underprivileged by lack of love, by the hardness of heart and barbarism.